Hawthorne effect on surgical studies. Issue 12 (16th October 2019) - Demetriou, Charis; Hu, Lisi; Smith, Toby O.; Hing, Caroline B.
Abstract: Background: The Hawthorne effect or 'observer effect' describes a change in normal behaviour when individuals are aware they are being observed. This may have an impact on effect estimates in clinical trials. The purpose of this study was to determine if the Hawthorne effect had been recorded as a risk of bias in surgical studies. Methods: A Preferred Reporting Items for Systematic Reviews and Meta‐Analyses compliant literature search was conducted till March 2019. Eligible studies included those reporting or not reporting the Hawthorne effect in surgical studies from the following databases: MEDLINE, Embase, CINAHL, AMED, BNI, HMIC, PsycINFO, Web of Science, Cochrane Library, Google Scholar and OpenGrey. Two reviewers independently reviewed the papers, extracted data and appraised study methods using the Newcastle Ottawa Scale or the Cochrane risk of bias tool. Data were analysed descriptively. Results: A total of 842 papers were identified, of which 16 were eligible. Six (37%) observational studies were identified with the aim of measuring the Hawthorne effect on their outcome with five reporting that the Hawthorne effect was responsible for the improvements in outcomes and one reporting no change in outcome due to the Hawthorne effect. Ten (63%) studies were identified, of which eight used the Hawthorne effect as an explanation to improvements seen in the control group or their secondary outcomes and two to compare their results with other studies. Conclusion: There is considerable between‐study heterogeneity on how the Hawthorne effect relates to surgical outcomes. Further consideration on reporting and considering the importance of the Hawthorne effect in the design of surgical trials is warranted. Abstract : A systematic literature search was performed to determine if the Hawthorne effect had been recorded as a risk of bias in surgical studies. There is considerable between‐study heterogeneity on how the Hawthorne effect relates to surgical outcomes. Further consideration on reporting and considering the importance of the Hawthorne effect in the design of surgical trials is warranted.